2012
DOI: 10.1038/ijo.2012.19
|View full text |Cite
|
Sign up to set email alerts
|

Energy restriction only slightly influences protein metabolism in obese rats, whatever the level of protein and its source in the diet

Abstract: BACKGROUND: High protein (HP) diets during energy restriction have been studied extensively regarding their ability to reduce body fat and preserve lean body mass, but little is known about their effects on protein metabolism in lean tissues. OBJECTIVE: To determine the effects of energy restriction and protein intake on protein anabolism and catabolism in rats. METHODS: For 5 weeks, 56 male Wistar rats were fed an obesity induction (OI) diet . They were then subjected to a 40% energy restriction using the OI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 51 publications
2
10
0
1
Order By: Relevance
“…In agreement with previous studies (Chevalier et al 2013;Jean et al 2001;Lacroix et al 2004), our research demonstrated some hyperproteic dietrelated changes, including persistent weight loss and lower food intake, an obvious reduction of plasma triglyceride and adipose tissue weight, and a decrease of plasma glucose and insulin in HPLC compared to MPMC rats. Thus, these parameters could be seen as phenotypes that can provide a reference for the application of nutrient interventions by protein supplement against hyperglycemia and hypercholesteremia.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with previous studies (Chevalier et al 2013;Jean et al 2001;Lacroix et al 2004), our research demonstrated some hyperproteic dietrelated changes, including persistent weight loss and lower food intake, an obvious reduction of plasma triglyceride and adipose tissue weight, and a decrease of plasma glucose and insulin in HPLC compared to MPMC rats. Thus, these parameters could be seen as phenotypes that can provide a reference for the application of nutrient interventions by protein supplement against hyperglycemia and hypercholesteremia.…”
Section: Discussionsupporting
confidence: 93%
“…Many studies have characterized the feeding-suppressive effect of a high-protein diet in rats starting the first day with a gradual adaptation during the following days (4,6,28,32). However, less is known on the efficacy of a high-protein diet to curtail spontaneous energy intake in diet-induced obese rats, as studies were set mainly in the context of an additional 40% energy restriction (1,12,18), making it difficult to analyze the respective contributions of these interventions. In the current study, the shifting from a 20% to a 52% protein diet markedly reduced the daily energy intake on the first day by 41% and 31% in the standard diet and DIO group, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…3A). During the remaining observation period (days [2][3][4][5][6][7][8][9][10][11][12][13][14], rats in the standard diet/standard diet group displayed an overall stable food intake with an average of 67.6 Ϯ 1.0 kcal/day (Fig. 3A).…”
Section: Western-type Diet Induces Obesitymentioning
confidence: 99%
“…42 13 C-valine enrichment in free and protein-bound amino acids, respectively, was determined as described previously. 42,43 Fractional synthesis rate (FSR, %/d) of colon protein was calculated as FSR ¼ Ebound val/(Efree val · t) · 100, where Ebound val and Efree val are the protein-bound and free 13 C-valine enrichments in the colon. Absolute synthesis rates (ASR, g/d) were calculated as ASR ¼ FSR · P, where P is colon protein content.…”
Section: Animals and Study Designmentioning
confidence: 99%